1997
DOI: 10.1038/nsb0897-644
|View full text |Cite
|
Sign up to set email alerts
|

Interlocking structural motifs mediate molecular discrimination by a theophylline-binding RNA

Abstract: To visualize the interplay of RNA structural interactions in a ligand binding site, we have determined the solution structure of a high affinity RNA-theophylline complex using NMR spectroscopy. The structure provides insight into the ability of this in vitro selected RNA to discriminate theophylline from the structurally similar molecule caffeine. Numerous RNA structural motifs combine to form a well-ordered binding pocket where an intricate network of hydrogen bonds and stacking interactions lock the theophyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
258
0
3

Year Published

1999
1999
2003
2003

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 278 publications
(275 citation statements)
references
References 43 publications
14
258
0
3
Order By: Relevance
“…Various aptamers were constructed containing the theophylline-binding core motif to determine which systems were suitable for NMR studies, and their ligand-binding affinities were measured at 25 8C+ The hairpin-loop region of the original ⌬TCT-4 theophylline-binding RNA (Jenison et al+, 1994) was observed to cleave over time in Mg 2ϩ -containing buffer (not shown); therefore other constructs (Fig+ 1B) containing the conserved core nucleotides and a stable GAAA-tetraloop motif were synthesized+ The sequence of the terminal stem was also changed in these constructs relative to the wild-type ⌬TCT-4 sequence to improve transcription and for compatibility with the sequence requirements for hammerhead ribozyme cleavage that was used to posttranscriptionally process the theophylline-binding RNAs to give a homogeneous 39 end (see Materials and methods)+ The ⌬-33 RNA contains a GAAA tetraloop with a flanking 3-bp stem connected to the conserved core, and this RNA has the same binding affinity for theophylline as the original wild-type ⌬TCT-4 sequence+ The ⌬-31 construct (Fig+ 1B) eliminates a single G•C pair adjacent to the theophylline-binding core, thus reducing the size of the RNA+ Comparative sequence analysis of the original in vitro selection experiment indicated that only 2 bp were required to close the upper stem (Jenison et al+, 1994)+ However, the ⌬-31 construct binds theophylline with a factor of ;15 lower affinity than the wild-type ⌬TCT-4 RNA (Fig+ 1B)+ This suggests that the GAAA tetraloop and the theophylline-binding core may need to be separated by a minimum number of helical residues so that the tetraloop does not affect the structure and/or dynamics of the core+ The ⌬-40 construct binds theophylline with approximately eight times lower affinity than the original ⌬TCT-4 aptamer or the ⌬-33 construct (Fig+ 1B)+ This result was very surprising because this RNA has the same sequence as ⌬-33, except for a flip of 2 bp in the hairpin stem flanking the conserved core region+ In the structure of the ⌬-33 RNA-theophylline complex, the G11 stacks on top of A10 within the core region of the complex (Zimmermann et al+, 1997)+ Thus flipping the G11-C20 pair replaces a stable purine-purine stack with a less stable pyrimidine-purine stack and may be the reason for the lower binding affinity for the ⌬-40 construct+ All possible base pair sequences were observed at this position in the original selection experiment (Jenison et al+, 1994), indicating that the isolates from in vitro selections contain a range of binding activities, and quantitative experiments are required to define more precisely the functionally important positions+ Functional group interference mapping is consistent with a U-turn U-turns are a common structural motif in RNA and are stabilized by intraturn base-backbone H-bonding interactions (Quigley & Rich, 1976;Jucker & Pardi, 1995)+ U24 is part of a U-turn in the core of this RNA aptamer (Zimmermann et al+, 1997) where the U24 29-hydroxyl is hydrogen bonded to the N7 of G26 (Fig+ 5A)+ As seen in Table 1, replacement of the U24 29-hydroxyl with 29-deoxy strongly inhibits the ability of the RNA to bind theophylline (.90-fold lower affinity), presumably by disrupting this U24 29OH-to-G26 N7 H-bond+ However, disruption of this H-bond by the 7-deaza, 29-deoxy G26 base modification has a much smaller effect on theophylline binding+ The effect of the 7-deaza substitution is most appropriately addressed by comparing relative binding affinities of 7-deaza, 29-deoxy G26 to 29-deoxy G26 (Table 1), where...…”
Section: Nucleotides Flanking the Core Can Affect Theophylline Bindingmentioning
confidence: 99%
See 3 more Smart Citations
“…Various aptamers were constructed containing the theophylline-binding core motif to determine which systems were suitable for NMR studies, and their ligand-binding affinities were measured at 25 8C+ The hairpin-loop region of the original ⌬TCT-4 theophylline-binding RNA (Jenison et al+, 1994) was observed to cleave over time in Mg 2ϩ -containing buffer (not shown); therefore other constructs (Fig+ 1B) containing the conserved core nucleotides and a stable GAAA-tetraloop motif were synthesized+ The sequence of the terminal stem was also changed in these constructs relative to the wild-type ⌬TCT-4 sequence to improve transcription and for compatibility with the sequence requirements for hammerhead ribozyme cleavage that was used to posttranscriptionally process the theophylline-binding RNAs to give a homogeneous 39 end (see Materials and methods)+ The ⌬-33 RNA contains a GAAA tetraloop with a flanking 3-bp stem connected to the conserved core, and this RNA has the same binding affinity for theophylline as the original wild-type ⌬TCT-4 sequence+ The ⌬-31 construct (Fig+ 1B) eliminates a single G•C pair adjacent to the theophylline-binding core, thus reducing the size of the RNA+ Comparative sequence analysis of the original in vitro selection experiment indicated that only 2 bp were required to close the upper stem (Jenison et al+, 1994)+ However, the ⌬-31 construct binds theophylline with a factor of ;15 lower affinity than the wild-type ⌬TCT-4 RNA (Fig+ 1B)+ This suggests that the GAAA tetraloop and the theophylline-binding core may need to be separated by a minimum number of helical residues so that the tetraloop does not affect the structure and/or dynamics of the core+ The ⌬-40 construct binds theophylline with approximately eight times lower affinity than the original ⌬TCT-4 aptamer or the ⌬-33 construct (Fig+ 1B)+ This result was very surprising because this RNA has the same sequence as ⌬-33, except for a flip of 2 bp in the hairpin stem flanking the conserved core region+ In the structure of the ⌬-33 RNA-theophylline complex, the G11 stacks on top of A10 within the core region of the complex (Zimmermann et al+, 1997)+ Thus flipping the G11-C20 pair replaces a stable purine-purine stack with a less stable pyrimidine-purine stack and may be the reason for the lower binding affinity for the ⌬-40 construct+ All possible base pair sequences were observed at this position in the original selection experiment (Jenison et al+, 1994), indicating that the isolates from in vitro selections contain a range of binding activities, and quantitative experiments are required to define more precisely the functionally important positions+ Functional group interference mapping is consistent with a U-turn U-turns are a common structural motif in RNA and are stabilized by intraturn base-backbone H-bonding interactions (Quigley & Rich, 1976;Jucker & Pardi, 1995)+ U24 is part of a U-turn in the core of this RNA aptamer (Zimmermann et al+, 1997) where the U24 29-hydroxyl is hydrogen bonded to the N7 of G26 (Fig+ 5A)+ As seen in Table 1, replacement of the U24 29-hydroxyl with 29-deoxy strongly inhibits the ability of the RNA to bind theophylline (.90-fold lower affinity), presumably by disrupting this U24 29OH-to-G26 N7 H-bond+ However, disruption of this H-bond by the 7-deaza, 29-deoxy G26 base modification has a much smaller effect on theophylline binding+ The effect of the 7-deaza substitution is most appropriately addressed by comparing relative binding affinities of 7-deaza, 29-deoxy G26 to 29-deoxy G26 (Table 1), where...…”
Section: Nucleotides Flanking the Core Can Affect Theophylline Bindingmentioning
confidence: 99%
“…The metal-binding site in the core of this RNA aptamer could perform a number of functions critical to theophylline binding and caffeine discrimination+ By stabilizing the high density of negative charge created by the juxtaposition of multiple phosphate groups (C22, U23, U24, G25) in this turn (Fig+ 6), the metal could facilitate folding of the core+ This is a critical region in the core of the RNA because it allows interactions between conserved residues of the two internal loops (Fig+ 1B) that are required for the formation of the ligandbinding pocket+ Residues U24, G25, and G26 are part of the U-turn (Quigley & Rich, 1976;Jucker & Pardi, 1995;Zimmermann et al+, 1997) that helps bring the upper and lower loops of the RNA together to form the ligand-binding site+ Another potential role for the metal (Zimmermann et al+, 1997), and the arrow points to the N7 of residue A28 that, when modified to 7-deaza, showed much lower affinity for theophylline (see text)+ is to correctly orient the bases of residues C22 and U24 that hydrogen bond to theophylline, forming the critical base-triple that mediates the molecular discrimination of this RNA aptamer (Zimmermann et al+, 1997)+ Although the data in Figures 3 and 6 clearly define the region of the metal-binding site, additional data such as thiophosphate interference-type experiments are needed to try to identify uniquely specific ligands on the RNA that are coordinating the metal+…”
Section: Nucleotides Flanking the Core Can Affect Theophylline Bindingmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of some secondary structural features in RNA serves to disrupt the regular helical geometry and, importantly, to expose functional groups capable of forming hydrogen bonds; the ultimate effect of this is to create potential binding sites for ligands, either intramolecular when folding to a higher order structure, or intermolecular involving either other RNA or protein molecules [9][10][11]. The elements of secondary structure largely involve the formation of base pairs both canonical and non-canonical, to form regular or distorted double helices.…”
Section: Introductionmentioning
confidence: 99%